Pengaruh Persepsi Label Halal Terhadap Preferensi Konsumen pada Restoran Pizza Hut dan KFC di Yogyakarta - Dewi Samad, Telsy Fratama (Falah: Jurnal Ekonomi Syariah, 2019)
Halal label has an important role to make consumers recognize easily the quality of products, especially to Muslim consumers. It has enhanced the image of products’s cleaness, purity, and no harm. The non-Muslims are also give positif feedback about halal label. This study aims to determine the consumers’ perseption of halal label, the effect perception of halal label on consumers purchasing preference at the Pizza Hut and KFC Restaurant. Determine whether there are differences in consumers' perception of halal label based on gender, religion, educational background, and income. Determine whether there are differences of influence on halal label perception based on gender, religion, education background and income to consumer preferences. This research is quantitative with 200 sample respondents Pizza Hut and KFC, simple random sampling method. The data collection using a likert scale questionaire. Data were analized using Correlation Analysis, Different T-test & F-test (Anova), and Analisis Multivariat Analysis Varians (Manova). The result found that overall average level of respondents's perception of halal label positif and has significant effect on the preferences. Then the result of analysis differences perseption found that there are significant differences between the consumers’ perseption of halal label based on gender, religion, educational background, while based income level, did not occur significantly different. The result analysis in effect, discover that there were significant differences influent perception of halal label on the characteristics of the consumers purchasing preferences: gender, religion, educational background, and income.